PENGARUH KREDIT USAHA RAKYAT TERHADAP PENDAPATAN UMKM (STUDI KASUS PADA USAHA MIKRO BINAAN BANK BRI CABANG TAMPAN PEKANBARU TAHUN 2014 (TW 1) – 2018 (TW 4) - Selfani, Rizki Sasqia; Anthony, Mayes; Any, Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of people's business credit onUMKM income (case study on BRI Micro Business Guiding Bank BRI HandsomeBranch in 2014 (Tw 1) - 2018 (Tw 4)). The method used in this research isdescriptive and quantitative methods. The analytical model used is nonparametricstatistics, nonparametric statistics consist of several parts, namely Paired SampleTTest. This test is used to determine whether there is an average differencebetween two groups of samples that are paired (related), which means a sample buthas two different treatments. Based on the results of research about the Effect ofGiving People's Business Credit (KUR) PT Bank BRI Pekanbaru HandsomeBranch Against Micro and Small Business Revenues (UMK) in the District ofTampan it can be concluded that there are differences in MSME income before andafter the Bank BRI People's Business Credit Handsome Branch Pekanbaru Year2014 (Tw 1) - 2018 (Tw 4).Keywords: Provision of People's Business Credit (KUR), BRI Bank, HandsomePekanbaru Branch